Health-based homophily in public housing developments - Brenda Heaton; Neha Gondal (BMC, 2023)
Abstract Public housing residents in the United States face disproportionately high risks for disease, presenting an urgent need for interventions. Evidence suggests interventions leveraging social networks can be successful when relationships are homophilous, as this leads to pooling of risk behaviors among interconnected alters. Yet, we know little about networks of public housing residents. To assess the feasibility of network-based interventions, we investigate the incidence of health-based homophily in public housing developments in Boston, Massachusetts. Employing multilevel models (HLM), we find that respondents report their own health characteristics to be similar to their network partners on oral health, weight, and consumption of sugar-sweetened beverages and foods. We discuss the implications of our findings for health-based interventions in low-income communities.